POTENSI PEMANFAATAN LAHAN TIDUR DALAM UPAYA MENDUKUNG KEBERLANJUTAN PROGRAM MHR (MENGELOLA HUTAN RAKYAT) ANTARA PT. MHP DAN WARGA SEKITAR - Serly Novita Sari; Fachrurrozie Sjarkowi; Arfa Afriana (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2017)
The purpose of this research for 1. Identify the potential of community land based on the size of the geophysical environment. 2. Analyze which combinations of commodities can be optimized to generate maximum income-income as an indicator of the realization of the MHR partnership. This research was conducted at Talang Ubi Sub-district Muara Enim Regency. This research was conducted from October 2016 until May 2017. The research method used is case study method with 46 farmers. Based on the results of research that has been done then can be drawn conclusion, as follows: 1. Potential of farmers' sleeping land in Talang Ubi Sub-district, still big enough that is 3.52 ha in average. With 58.7% of the land owned by farmers is considered flat, and 30.43% of the land is classified as sloping, and the remaining 10.87% is considered steep, and the physical condition of the land suitable for planting acacia. 2. The combination of recommended crop commodities on the farmers' sleeping land to meet the maximum revenue target, and land cultivation is the acacia, jengkol and banana commodities in the Planting Group I (K MT) I, Cassava Seasons I (MT) I at K MT II, (MT) I and II at MT II and III, Plant Seeds I (MT) I at MT IV K and MT II and III beans on K MT V and VI. Revenue expectations of farmers has reached the expected target of Rp85.954.681,41 which means that when viewed from the conditions of income expectations, partnership patterns MHR will be easy to build.